LDL-cholesterol: Friedewald calculated versus direct measurement-study from a large Indian laboratory database - Kannan, Subramanian (Medknow Publications & Media Pvt Ltd, 2014)
BACKGROUND: Validity of Friedewald formula (FF) in patients with serum triglycerides (TGs) <400 mg/dl is unclear. MATERIALS AND METHODS: We compared low-density lipoprotein (LDL)-cholesterol calculated by FF to directly measured LDL in a laboratory database of 14,620 lipid profile samples from south India. RESULTS: LDL by FF correlated with directly measured LDL with correlation coefficient of 0.89 with the best correlation seen in TG levels 100-150. Higher level of TG (>200) underestimates the LDL calculated by FF particularly at LDL values <70 mg/dl. On the other hand, LDL is overestimated by FF in more than 70% of cases at LDL levels >130 mg/dl. CONCLUSION: We suggest repeating the LDL by direct assay techniques particularly in patients with TG >200 and when LDL <70 or >130. This helps in correctly stratifying the coronary artery diseases’ (CADs’) risk and goals of treatment.